Central Precocious Puberty in a Child With Metachromatic Leukodystrophy - Belli, Gilda; Bartolini, Emanuele; Bianchi, Andrea; Mascalchi, Mario; Stagi, Stefano (Frontiers in Endocrinology, 2018)
Metachromatic leucodystrophy (MLD) is a rare inherited lysosomal disorder caused by reduced activity of the enzyme arylsulfatase A with accumulation of sulfatides in the nervous system. We report a female child affected by MLD who developed central precocious puberty (CPP). This association has not been described so far. The proposita, after normal growth and psychomotor development, at age of 30 months presented with a rapidly progressive gait disturbance with frequent falls and with loss of acquired language skills. Magnetic resonance imaging showed leukoencephalopathy. Biochemical blood essays showed a 91% reduction in the arylsulfatase A activity and genetic analysis revealed compound heterozygous mutations of the Arylsulfatase A gene, enabling diagnosis of MLD. Subsequently, the patient had further rapid deterioration of motor and cognitive functions and developed drug-resistant epilepsy. At 4 years and 7 months of age a bilateral thelarche occurred. Magnetic resonance imaging showed a small pituitary gland, extensive signal changes of the brain white matter, increased choline, decreased N-acetyl-aspartate and presence of lactate on 1HMR spectroscopy. The hormonal profile showed increased 17-Hydroxyprogesterone and 17beta-oestradiol. Pelvic ultrasound demonstrated a slightly augmented uterine longitudinal diameter (42 mm). The gonadotropin-releasing hormone stimulation test revealed a pubertal LH peak of 12.9 mUI/ml. A diagnosis of CPP was made and treatment with gonadotropin-releasing hormone agonists was initiated, with good response. In conclusion, a CPP may occur in MLD as in other metabolic diseases with extensive white matter involvement. We hypothesize that brain accumulation of sulfatides could have interfered with the regulation of the hypothalamic-pituitary axis by triggering CPP in our patient.